Periodo de luz solar en el comportamiento fenotípico de Coriandrum sativum l. en casa Malla Aluminet. Loreto - Pinedo Jiménez, Julio (2021)
The coriander considered one of the most aromatic species in the world; Its management under protection allows to improve its vegetative adaptation, the main objective was to determine the effect of the periods of sunlight on the phenotypic behavior of Coriandrum sativum L. in aluminet mesh house, it seeks to take better advantage of the genetic potential when growing in protected environments. The completely Random Design was used with the treatments: open field (T0), aluminet house solar light from 9.0 am (T1), aluminet house solar light all day (T2), aluminet house solar light until 3.0 pm (T3). Direct sowing was carried out with a continuous stream, in rows 3.0 cm deep and 3.0 cm wide in an approximate amount of 50 seeds per furrow of 1.0 m long, the seeds were covered with the soil for their germination. The open field cultivation showed higher averages than under the aluminet mesh house at plant height with 23.20 cm. The length of the roots, the diameter of the bundle, the number of plants per bundle and the total bundle weight are shown to be indifferent to the growing environments. The averages indicate good behavior of the coriander under the aluminet house compared to open ground, number of plants per bundle 157.40 and 106.8, total bundle weight 477.80 and 398.40 g respectively.